Copeptin assays in children for the differential diagnosis of polyuria‐polydipsia syndrome and reference levels in hospitalized children. (25th October 2021) - Bonnet, Laura; Marquant, Emeline; Fromonot, Julien; Hamouda, Ilyes; Berbis, Julie; Godefroy, Alice; Vierge, Melody; Tsimaratos, Michel; Reynaud, Rachel
Abstract: Objectives: Polyuria‐polydipsia syndrome (PPS) is a common presentation in children but the differential diagnosis rests on burdensome water deprivation tests. The aims of this study were to determine a copeptin threshold to distinguish patients with central diabetes insipidus from those with primary polydipsia and to estimate the normal range of copeptin concentrations in children. Design: Single‐centre retrospective descriptive study. Patients: Two hundred and seventy‐eight children aged 2 months to 18 years who consulted for PPS ( N = 40) or other reasons (control group, N = 238) at La Timone University Hospital in Marseille, France, between April 2015 and September 2019 and had a copeptin assay. Measurements: Ultrasensitive copeptin assays on blood samples. Results: Among the children with PPS, the mean copeptin concentrations were 1.72, 55.2 and 15.7 pmol/l in those with central diabetes insipidus ( N = 21), nephrogenic diabetes insipidus ( N = 3), and primary polydipsia ( N = 16), respectively. Copeptin levels lower than 3.53 pmol/l were diagnostic of central diabetes insipidus with 100% sensitivity and 87.4% specificity ( p < .001). The 5th–95th copeptin percentile range in the control group was 2.53–21.03 pmol/L. Copeptin levels were significantly higher in boys than in girls but there was no association with age, pubertal stage, body mass index, or the reason for consulting. Conclusions: Our results indicate copeptin assays may be valuable in the differential diagnosis of PPS in children. Larger prospective studies are required to establish their accuracy in everyday clinical practice.